Peran Orang Tua Sebagai Pemberi Informasi Kesehatan Reproduksi pada Remaja - C, Risma Anuril; Wulandari, Lisa Purbawaning; Tarsikah, Tarsikah (Poltekkes Kemenkes Malang & IBI Ranting Pendidikan Kota Malang, 2023)
The most important problem of adolescent reproductive health (KRR) in Indonesia is the lack of information about reproductive health, shifts in adolescent sexual behavior, poor health services and unsupportive legislation. The problem is, parents who are considered experts and experienced, have obstacles in sharing experiences due to socio-cultural factors. The purpose of this study was to describe the role of parents as providers of reproductive health information to adolescents. The research method used descriptive with a total sample of 88 respondents who were parents of teenagers aged 10-14 years in Petungsewu Village, Dau District, Malang Regency. The sampling technique used simple random sampling technique. Data collection using a questionnaire. Data analysis was performed using a frequency distribution. The results of this study were that parents played a good role in providing information about adolescents' physical changes, namely 65.9%, played a less role in providing information about adolescents' psychological changes, namely 46.6%, played a less role in providing information about the care of adolescents' reproductive organs, namely 44.3%, play a sufficient role in providing information about adolescent reproductive health problems, namely 50%, and play a less role in providing information about adolescent risky sexual behavior, namely 44.3%. Parents have an important duty and role because parents are the first and foremost teachers in educating teenagers.